SMART CONTRACT-DRIVEN QUEUE MANAGEMENT FOR EFFICIENT ONLINE TICKET PURCHASING ON BLOCKCHAIN - Puspitaningtyas, Mery Oktaviyanti; Ilmi, Happid Ridwan; Wardani, Yulita Ayu; Saputra, Irwansyah (STKIP PGRI Tulungagung, 2025)
This study investigates how smart contract-driven queue management can be utilized to increase online ticket purchasing efficiency via blockchain technology. The system is designed to manage ticket purchase queues transparently and securely, using smart contracts written in the Solidity programming language and the Ionic UI framework. In addition, the system is connected with MetaMask as a transaction wallet, allowing users to purchase tickets directly and securely. Ganache serves as a testing environment for replenishing wallet balances without involving real transactions. The First In First Out (FIFO) approach is used to manage the transaction queue, with the first purchased ticket being processed first by the administrator. The administrator accepts each transaction, which is then confirmed by MetaMask. When the transaction is confirmed, the system automatically updates the ticket status. The implementation results show that this system effectively optimizes ticket transaction management transparently and securely. This work also makes a significant contribution to the application of blockchain technology for better management of online ticket purchasing systems, as well as minimizing the possibility of transaction errors and fraud.